Pengaruh Self-Service Technology Terhadap Kepuasan Nasabah Bank BCA KCP Depok Asri - Novisha, Dewi; Suardy, Weman (Jurnal Informatika Kesatuan, 2023)
The rapid advancement of technology and information requires banks to further develop the quality of services in Digital Banking in their operational activities. The development of technology and information in the world makes the banking business very competitive, which has an impact on global economic growth. Therefore, the banking industry utilizes Digital banking which consists of Internet Banking and SMS Banking. both facilities include Self Service Technology (SST) services. The purpose of this study is to determine whether the Self Service Technology (SST) facility consisting of Internet Banking and SMS Banking affects customer satisfaction. This research uses quantitative research. The data analysis method uses multiple linear regression analysis methods, t-test, f test and coefficient of determination (r2) analysis as well as spss 16.0 application assistance. Based on the results of the study, it shows that the Internet Banking variable with a calculated value of 2,642 is greater than the t-table value of 1.984 and the significance value of 0.010 is smaller than 0.05. then Ho was rejected and Ha was accepted. This means that SMS Banking has a positive and significant effect on Customer Satisfaction. Internet Banking variable with a calculated value of 5,010 is greater than the t-table value of 1,984 and its significance value of 0.000 is less than 0.05. This means that SMS Banking has a positive and significant effect on Customer Satisfaction. Furthermore, the results of the f-test showed an f-count value of 5,010 greater than the f-table of 1.984 and a significant value of 0.000 smaller than 0.05. So it can be concluded that the influence of Internet Banking and SMS Banking has a joint effect on Customer Satisfaction of Bank BCA KCP Depok Asri. Keywords: Self Service Technology, Internet Banking, SMS Banking and Customer Satisfaction.